Role of Phosphorus Source and Biochar Levels on Some Fertility and Productivity Characteristics of Barley Crop Grow in Gypsiferous Soils - Hilal, Nashmi Ahmed; Khalaf, Ahmed Ibrahim; Alwan, Afrah Abdul Kareem Hussein (American Journal of Botany and Bioengineering, 2026)
A Factorial Field experiment was conducted in Kirkuk governorate / plastic house of follower for the plant production department in technical institute – Hawija during the winter season to study the effect of phosphate source and biochar level in some fertility and productivity characteristics of barley crop planted in three gypsoferous soils. The experiment included three factors: the first factor is phosphoruse source (Triple super phosphate and Rock phosphate) and at the level (120) Kg P ha-1 for both , the second factor is biochar (0 , 0.5, 1)% , the third factor is gypsum content of soils (5.12 , 11.76 , 17.9) %. The experiment was designed according to RCBD and with three repetitions. The results showed The phosphorus source, soil content of gypsum and biochar level significantly affected the productivity and fertility features, The highest average concentration of nitrogen, phosphorus, organic matter, grain yield came from the interaction of triple super phosphate fertilizer (120) Kg P ha-1 , 1% level of biochar and soil with 5.12 % gypsum content and reached (33.08) mg Kg-1 , (40.12) mg Kg-1 , (10.73) g Kg-1 , (38.19) g pot-1 respectively.